High-Frequency Percussive Ventilation: A Promising Rescue Strategy in Severe Lung Disease of Extremely Low Gestational Age Neonates - Kevin Louie; Kristina Ericksen; Lance A. Parton (MDPI AG, 2024)
Objective: The aim of this study was to evaluate high-frequency percussive ventilation (HFPV) as a rescue strategy for extremely low gestational age neonates (ELGANs) with severe lung disease. Methods: This is a retrospective review of 16 ELGANs with severe lung disease who were placed on HFPV following a lack of improvement on other modes of conventional and high-frequency ventilation. Results: The gestational age of these 16 infants was 25 (24, 26) weeks and their birth weight was 640 (535, 773) grams [median (IQR)], with the survivors being more immature compared to those who died [24 (23, 26) and 26 (25, 28) weeks, respectively; (p = 0.04)]; and with an overall mortality of 31% (N = 5). Of those who died, 60% were SGA (p = 0.02). Following placement on HFPV, the survivors had a statistically significant decrease in their respiratory severity scores (RSSs) [11 (9, 14) to 6 (5, 13), p = 0.03] compared to those who did not survive [15 (11, 16) to 11 (6.8, 14.5), p = 0.32] due to an improvement in their oxygenation [FiO2: 0.95 (0.85, 1) to 0.6 (0.4, 0.9), p = 0.01; compared to 1 (1, 1) to 1 (0.7, 1); survivors and non-survivors, respectively; p = 0.32]. Chest X-rays also showed significantly improved aeration due to decreased areas of atelectasis in those who survived. Conclusions: HFPV may be an appropriate rescue mode of high-frequency ventilation in the ELGAN population with severe lung disease, particularly for patients with impaired oxygenation and ventilation difficulties due to shifting atelectasis and mucous plugging.